Penerapan Tingkat Sanitasi Dan Higien Pada Prodak Perikanan Segar Di Pasar Tradisional Cirebon - , NENIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the application of sanitary and hygiene merchant fishery products in traditional markets Cirebon. Selection of market samples used simple random sampling method (simple random sampling). Quantitative descriptive analysis of the data is used to describe the application of the principle of the questionnaire level of sanitation and hygiene in traditional Cirebon. BNT with a confidence level of 95% is used to analyze data and test results TPC (Total Plate Count). In general, the application of sanitary and hygiene of fish traders in traditional markets Cirebon are low levels, some of them are not applied sanitation and hygiene properly. It can be seen from the average total point questionnaire, the traditional market Cirebon has an average total of 2.14 (less than 3 points). Based on the results of TPC, TPC Market Kramat has the best value that is equal to 2.9 x104 cfu / g. The market with intermediate TPC number is pasar Kalitanjung and pasar Sumber, which is amount to 5,2 x104 cfu/g 9,2 x104 cfu/g, and pasar Pasalaran (Plered), have a worst total value which is amounted to TPC 7x105 cfu/g. Pasar Pasalaran (Plered) TPC value doesnât meet the limit of Indonesian National Standard (SNI) or exceeding the maximum limit (5x105 cfu/g) while the other traditional market sample meet the boundaries Indonesian National Standard (SNI) or doesnât exceeding the maximum limit (5x105 cfu/g). Based on the results BNT test 5%, in each sample traditional market in Cirebon with an average number of bacteria was significantly different. Based on results analysis of variance at traditional markets Cirebon showed that a duncan grouping A, B, C, and D which means every sample in Cirebon traditional market is significantly different.